Optimization of image mapping & camera coverage efficiency for continuous location and tracking - Avinash A.R.; Chandan K.C. (2023)
The Vision Based location and tracking is a vastly escalating technology mainly used to monitor various environments. This technology can be briefly divided to 3 parts which is the localization of image sensors (cameras), maximizing the total area of vision and the locating and tracking of other objects. Initially only one GPS camera is used for reference and timing purposes. By using the image mapping technique distance between 1st and 2nd camera can be obtained. Thus by knowing the rotation angle of the 2nd camera to locate the first camera, the 2nd camera can be localized .This same method is used for the other cameras to localize itself. Finally when all cameras are localized tracking of objects can proceed. Simulation done using Matlab has proved the significance of image mapping method (error=1.3%), iteration algorithm (error=5.98%) and velocity tracking (error=0.52%) when results of simulation was compared to actual measurement. 2009 IEEE.